BERPIKIR KRITIS SISWA BERKEPRIBADIAN SENSING, INTUITION, THINKING DAN FEELING DALAM MENYELESAIKAN MASALAH DENGAN INFORMASI KONTRADIKSI - Kurniati, Dian; Umami, Anggi Nabilla; Murtikusuma, Randi Pratama; Setiawan, Toto Bara; Jatmiko, Dhanar Dwi Hary (Department of Mathematics Education, Universitas Kuningan, 2023)
Critical thinking skill is necessary to be learned by every students, because by thinking critically students are able to understand other mathematical skills. One of the problems that can improve critical thinking skills is Problem With Contradiction Information (PWCI), which means problem that contains wrong information. Every student has their own characteristics, it also influences their critical thinking. One of the ways to identify a type of personality people is by using the Myers Briggs Type Indicator (MBTI), which classifies humans based on several perspectives, such as how to understanding and receiving information (Sennsing-Intuition), also how to make a conclusion and decision (Thinking-Feeling). The purpose of this study is to describe the critical thinking skills of students with sensing, intuition, thinking and feeling personalities. This research is a descriptive study with a qualitative approach. This research was based on SMAN Arjasa, and the subject was 8 students consisting of 2 students each with sensing, intuition, thinking and feeling personality. Data collection methods used are test and interview. The analysis technique used is the analysis of test results, interviews and triangulation. The results of this research revealed that students with sensing, intuition, thinking and feeling personality types have their own characteristics when solving the problem. The results of the critical thinking test found that there were no students who were able to fulfill critical thinking skills but there were students who were able to find contradictory information in the question